New device multisegment Mechanical Thrombectomy System for endovascular treatment in acute ischaemic stroke: study protocol for a prospective, multicentre, randomised controlled trial. Issue 11 (16th November 2022) - Zhong, Hailong; Li, Zhaoshuo; Zhou, Tengfei; Li, Tianxiao; He, Yingkun
Abstract : Introduction: Endovascular treatment is the standard of care for acute large vessel occlusion (LVO) in the anterior circulation. However, successful complete recanalisation is considerably difficult when the vessels are severely tortuous. At the bend, the stent retriever can distort, collapse and lose its ability to capture the clot due to structural change. The aim of the present study is to evaluate the safety and efficacy of the new thrombectomy device multisegment Mechanical Thrombectomy (MT) System for endovascular treatment of acute ischaemic stroke (AIS). Methods and analysis: The present study is a prospective, multicentre, randomised controlled trial conducted in 11 stroke centres in China. The safety and efficacy of vascular recanalisation in patients with AIS who will be treated with a new thrombectomy device-multi-segment MT System or with Solitare FR within 8 hours of symptom onset will be compared. A total of 238 subjects who met the inclusion and exclusion criteria will be randomised into either a treatment group or a control group by an internet-based Central Random System in a 1:1 manner, and 30 subjects will be recruited into the small sample study. SAS V.9.4 statistical software will be used for statistical analysis of the primary endpoint indicators and other indicators. Ethics and dissemination: The study involving human participants was reviewed and approved by the Ethics Committee of Drugs (devices) Clinical Experiment in Henan Provincial People's Hospital (reference number: AF/SC-07/04.0) and other research centres participating in the clinical trial. The results yielded from this study will be presented at international conferences and sent to a peer-review journal to be considered for publication. The Standard Protocol Items: Recommendations for Interventional Trials checklist was utilised when drafting the study protocol. Trial registration number: Registry on 10 September 2021 with Chinese clinical trial registry: ChiCTR2100051048.